2022
DOI: 10.1097/lgt.0000000000000710
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopy Standards: Guidelines for Endocervical Curettage at Colposcopy

Abstract: ObjectiveThe most recent guidelines for colposcopy practice in the United States, the 2017 Colposcopy Standards Consensus Guidelines, did not include recommendations for endocervical curettage (ECC). This document provides updated guidelines for use of ECC among patients referred for colposcopy.MethodsConsensus guidelines for the use of ECC were developed in 2012. To update these guidelines in concordance with the 2017 Colposcopy Standards process, an expert workgroup was convened in 2021. Literature had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…However, biopsy may be deferred for low-risk patients, defined as cytology of NILM, ASC-US, or LSIL, no evidence of HPV-16 or -18 infection, and no visible abnormalities. In addition to biopsies of all acetowhite areas, sampling of the endocervical canal with endocervical curettage is recommended for high-grade cytology (ASC-H, HSIL, or AGC), HPV-16 or -18 infection, positive results on dual stain, following precancer treatment, during observation of CIN2, and when the squamocolumnar junction is not fully visualized; endocervical curettage is preferred for those aged 40 years or older . During pregnancy, biopsies should be deferred unless there is concern for cancer, and endocervical curettage is contraindicated …”
Section: Discussionmentioning
confidence: 99%
“…However, biopsy may be deferred for low-risk patients, defined as cytology of NILM, ASC-US, or LSIL, no evidence of HPV-16 or -18 infection, and no visible abnormalities. In addition to biopsies of all acetowhite areas, sampling of the endocervical canal with endocervical curettage is recommended for high-grade cytology (ASC-H, HSIL, or AGC), HPV-16 or -18 infection, positive results on dual stain, following precancer treatment, during observation of CIN2, and when the squamocolumnar junction is not fully visualized; endocervical curettage is preferred for those aged 40 years or older . During pregnancy, biopsies should be deferred unless there is concern for cancer, and endocervical curettage is contraindicated …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of Schneider et al [ 15 ] and Shepherd et al [ 16 ], who found that ECC was of most benefit to women older than 50 years, in terms of decreasing the incidence of cervical cancer and mortality. In the latest standarizing colposcopy guidelines, it is suggested to American practitioners that all patients over 40 years old should initially choose cervical curettage [ 8 ]. However, there is still no united view of the cut-off age and studies of more varied ethnicities are required to understand this.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that an ECC abnormality is an independent risk factor for residual disease after LLETZ [ 35 , 36 ]. However, the latest guidelines stipulate that if a subsequent resection is planned, the sampling device should not be placed in the cervical canal [ 8 ]. Therefore, attention should be paid to the results of ECC, follow-up monitoring should be strengthened, and risk factors should be considered in the selection of individualized diagnostic and treatment methods, which may play an active role in cervical intraepithelial neoplasia and residual tumors after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following is a summary of the ASCCP recommendations for the use of ECC. 41 ECC recommended: The ASCCP has created and maintains a clinical decision support tool for clinicians. 42 The ASCCP tool is available as a website (free of charge) or phone app (~$10 USD).…”
Section: Endocervical Curettagementioning
confidence: 99%